2009
DOI: 10.1139/x09-069
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in a chronosequence of Scots pine stands in a reclaimed opencast oil shale mine

Abstract: Ecosystems that develop on mine spoil can serve as significant sinks for CO2. The aim of this study was to estimate the rate of carbon accumulation and its distribution along forest ecosystem partitions in young Scots pine ( Pinus sylvestris L.) plantations in the Narva oil shale opencast, Estonia. The tree layer was measured in 2004 in 13 stands afforested with 2-year-old seedlings during 1968 to 1994. Three stands (afforested in 1990, 1983, and 1968) were selected for detailed analysis of the carbon sequestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“…These results are in accordance with the results of Ågren and Knecht (2001) and Norgren (1996), who reported that lodgepole pine allocates a larger proportion of aboveground biomass to the needles than Scots pine. Our results of aboveground biomass allocation in young Scots pine and lodgepole pine are in accordance with data published by other researchers for Scots pine (Xiao and Ceulemans 2004;Karu 2005) and for lodgepole pine (Turner et al 2004). We found that lodgepole pine allocated 27% of the aboveground biomass to the stem and Scots pine 31%; however, the mean stem mass of lodgepole pine was greater than that of Scots pine (respectively 282.2 and 245.0 g).…”
Section: Growth and Biomasssupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with the results of Ågren and Knecht (2001) and Norgren (1996), who reported that lodgepole pine allocates a larger proportion of aboveground biomass to the needles than Scots pine. Our results of aboveground biomass allocation in young Scots pine and lodgepole pine are in accordance with data published by other researchers for Scots pine (Xiao and Ceulemans 2004;Karu 2005) and for lodgepole pine (Turner et al 2004). We found that lodgepole pine allocated 27% of the aboveground biomass to the stem and Scots pine 31%; however, the mean stem mass of lodgepole pine was greater than that of Scots pine (respectively 282.2 and 245.0 g).…”
Section: Growth and Biomasssupporting
confidence: 92%
“…Magnani et al (2000) in their study of Scots pine stands of different age found that maximum aboveground primary Current-year 1-year-old Density of needles, per cm Scots pine Lodgepole pine Fig. 6 Density of needles on current-year and 1-year-old shoots of Scots pine and lodgepole pine production occurs at the age of 14-18 years with the height of trees 7.7-9.9 m. Karu (2005) found that the height, diameter, and biomass increment of Scots pine begins to decrease at the age of 25 and at the height of 6-8 m.…”
Section: Growth and Biomassmentioning
confidence: 97%
“…There is some concern about the risk of soil organic C loss resulting from human activity during forest establishment (Karu et al 2009). Forests generate much higher organic inputs to the soil through root and foliar litters; therefore, the lack of difference in soil organic matter between the two land uses may indicate an initial loss of soil C that has gradually been corrected over the past 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Total 5 replicate of samples were collected from the study site. Samples were dried in an oven at 80°C to constant weight to obtain the moisture free dry weight as followed by others (Karu et al 2009;Singh et al 2011) and expressed as Mg ha -1 C stock was calculated by multiplying a factor 0.4 assuming 40 % carbon present in the litter.…”
Section: Collection Of Understorey Vegetation and Litter And Estimatimentioning
confidence: 99%
“…In the present study, carbon stored in the understorey vegetation and litter components was 0.98 Mg C ha -1 , which is lower than other reported values. (Karu et al 2009;Pragasan and Parthasarathy 2005). C stock in litter component of reclaimed minesoil of Midwestern and Appalachian coalfields (USA) comprised of pine, hardwood and mixed stand was estimated 21.2, 14 and 6 Mg ha -1 respectively (Amichev et al 2008).…”
Section: Stock In Understorey Vegetation and Litter And Co 2 Sequesmentioning
confidence: 99%